(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The process of thermal diffusion boriding is well known and used throughout the world. It has a number of unique properties, such as high hardness and wear resistance under abrasive wear conditions. Continuous boride layers have increased brittleness, which is related with the elastic properties of borides. In this work, we studied the features of the formation of surface layers onlow-carbon steels after electro-spark alloying, and not by continuous processing of the entire surface of the steel, but only sections and subsequent thermal diffusion boriding from powder medium. Such complex technology enables to form discrete regular and irregular layers, which have a number of advantages, in particular, reduced brittleness. The structure and phase composition of the combined coating growth kinetics of the diffusion layer during the thermal diffusion boriding, are investigated. The creation of the considered composite layers with FeB and Fe2B phases with reduced brittleness will significantly expand their area of application, for example, for working conditions with moderate impact loads.